2021
DOI: 10.3390/v13020281
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic SARS-CoV-2 Cycle Threshold Value Predicts Disease Severity, Survival, and Six-Month Sequelae in COVID-19 Symptomatic Patients

Abstract: To date, there is no severe acute respiratory syndrome coronavirus 2- (SARS-CoV-2)-specific prognostic biomarker available. We assessed whether SARS-CoV-2 cycle threshold (Ct) value at diagnosis could predict novel CoronaVirus Disease 2019 (COVID-19) severity, clinical manifestations, and six-month sequelae. Hospitalized and outpatient cases were randomly sampled from the diagnoses of March 2020 and data collected at 6 months by interview and from the regional database for COVID-19 emergency. Patients were str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 53 publications
7
56
1
2
Order By: Relevance
“…Our finding that the score was associated with the time from illness onset (score lower with greater time from onset of illness) and CT (qPCR) on nasal swabs (score higher with greater viral burden on the nasal swab) suggest initial biological plausibility for the responsiveness of the score to clinical disease/viral burden. Other studies have shown an independent relationship between qPCR CT and disease outcome [34][35][36][37][38]. We did not find any direct relationship between the disease score and indicators of disease severity.…”
Section: Discussioncontrasting
confidence: 83%
“…Our finding that the score was associated with the time from illness onset (score lower with greater time from onset of illness) and CT (qPCR) on nasal swabs (score higher with greater viral burden on the nasal swab) suggest initial biological plausibility for the responsiveness of the score to clinical disease/viral burden. Other studies have shown an independent relationship between qPCR CT and disease outcome [34][35][36][37][38]. We did not find any direct relationship between the disease score and indicators of disease severity.…”
Section: Discussioncontrasting
confidence: 83%
“…Our findings are supported by previous reports that have shown SARS-CoV-2 Ct values in NP swabs to be predictive of disease severity and worse outcomes [8][9][10][11]. SARS-CoV-2 Ct in NP swabs is an appealing method as it is easily accessible and used in most algorithms for COVID-19 diagnosis on hospital admission.…”
Section: Discussionsupporting
confidence: 89%
“…Secondly, confusion surrounds the terminology used by studies assessing COVID-19 severity and the amount of virus at diagnosis. Once again, what has been found to predict COVID-19 severity is not the viral inoculum but the amount of virus that is locally replicating since at least few days before detection, as the shorter median period from disease onset to swab collection among the studies is 5 days (de la Calle et al, 2021;Trunfio et al, 2021). No evidence is yet available on the quantitative change from the amount of the viral inoculum to the amount of detected virus at symptom onset nor at diagnosis to support or reject this hypothesis, but the epistemological difference is substantial.…”
Section: Viral Replication Cut-offmentioning
confidence: 99%